Synthesis, Characterization, Photoluminescence Property of Al(III) Schiff Base Complexes and Their Applications in Forensic Fingerprint and Dye Sensitized Solar Cells - Srinivas, M.; Sulochana, N.; Ramesh, G.; Rajegowda, H.R.; Mahadevan, K.M.; Neelagund, Shivayogeeswara (Asian Journal of Chemistry, 2020)
Aluminium(III)-Schiff base complexes of bis(salicylidene)phenyl-1,2-diamino organic ligand derivatives were synthesized by condensation reaction with salicylaldehyde, substituted phenyl-1,2-diamine with aluminum trichloride and characterized by 1H NMR, FTIR, EDS and ICP-AAS. Photophysical properties like photoluminescence (PL) and IV characteristics were studied for the dye-sensitized solar cells (DSSCs) performance. The latent forensic finger print developments have also been demonstrated from the synthesized complexes. Photoluminescence studies revealed that emission peaks of the complexes in solution state appeared at 418-572 nm and emitted blue and pale-yellow light. Latent fingerprint detection study indicated that the powder compounds show a good adhesion and finger ridge details without back ground staining. Based on these results, these Al(III) complexes can serve as a suitable non-dopant blue light as well as pale yellow light emitting compound for flat panel display applications and applied to detect latent fingerprints on variable substrates.